2016
DOI: 10.1016/j.psyneuen.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous system contributes to enhanced corticosterone levels following chronic stress

Abstract: Exposure to chronic stress often elevates basal circulating glucocorticoids during the circadian nadir and leads to exaggerated glucocorticoid production following exposure to subsequent stressors. While glucocorticoid production is primarily mediated by the hypothalamic–pituitary–adrenal (HPA) axis, there is evidence that the sympathetic nervous system can affect diurnal glucocorticoid production by direct actions at the adrenal gland. Experiments here were designed to examine the role of the HPA and sympathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 66 publications
4
42
0
Order By: Relevance
“…It is currently unknown whether chronic stress directly affects GR levels in aged mice ( Gjerstad et al, 2018 ; Mifsud and Reul, 2018 ). In the present study, stress elevated the corticosterone level in the blood, which is consistent with the results of a previously described study ( Lowrance et al, 2016 ). Necrostatin-1 had no effect on the corticosterone level in stressed mice.…”
Section: Discussionsupporting
confidence: 94%
“…It is currently unknown whether chronic stress directly affects GR levels in aged mice ( Gjerstad et al, 2018 ; Mifsud and Reul, 2018 ). In the present study, stress elevated the corticosterone level in the blood, which is consistent with the results of a previously described study ( Lowrance et al, 2016 ). Necrostatin-1 had no effect on the corticosterone level in stressed mice.…”
Section: Discussionsupporting
confidence: 94%
“…7C, IPETT), indicating that physical exercise and stress training had differences in regulating EPI sensitivity of blood glucose. Studies have shown that chronic stress increased sympathetic nervous activity and elevated basal corticosterone levels and rapid glucocorticoid production (Lowrance et al, 2016). However, chronic exercise enhanced HPA-axis negative feedback and thus reduced HPA responses to stress or next bout of exercise (Hare et al, 2014).…”
Section: Myonectin Kncokdown Reverses the Beneficial Effects Of Stresmentioning
confidence: 99%
“…Chronic stress and exercise are both important exogenous factors to induce the activation of HPA axis. Chronic stress increased sympathetic nervous activity and elevated basal corticosterone levels and rapid glucocorticoid production, so stress exposure increases blood glucose via the activation of HPA axis (Lowrance et al, 2016). However, chronic exercise enhanced HPA-axis negative feedback and thus reduced HPA responses to stress or next bout of exercise (Hare et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of these systems may be associated with altered behavior [4], hormonal signaling [5] as well as changes in the immune system, for review see [6]. Environmental stressors may promote myelopoiesis in the bone marrow [7], glucocorticoid (GC) resistance in the brain and the spleen [8], increased circulatory levels of cytokines [9] and altered inflammatory profile in the brain [10].…”
Section: Introductionmentioning
confidence: 99%